Diffusion from a point source using power law of wind speed (MAUSAM, 2013)
bl 'kks/k i= esa ,d 'kgjh ok;q eaMy dks ,d lzksr fcUnq eku dj inkFkZ ds folj.k ds fy, ,d ekWMy laLFkkfir fd;k x;k gSA blds fiPNd dks ,d ifjHkkf"kr voLFkk ekuk x;k gS tgk¡ bldh lkanzrk 'kwU; gks tkrh gSA LFkkf;Ro Jsf.k;ksa dh miyC/k rduhdksa }kjk ikoj ykW dk mi;ksx djrs gq, m/okZ/kj iou vi:i.k dks vkdfyr fd;k x;k gSA bl ekWMy esa vkdfyr lkanzrkvksa dh rqyuk vUos"k.kdrkZvksa ds QhYM izs{k.kksa ls izkIr fd, x, fu"d"kksZa ds lkFk dh xbZ gSAIn the present paper, a model for the diffusion of material from a point source in an urban atmosphere is incorporated. The plume is assumed to have a well-defined edge at which the concentration falls to zero. The vertical wind shear is estimated using power law, by employing most of the available techniques of stability categories. The concentrations estimated from the model were compared favorably with the field observations of investigators.